All star sales teams : 8 steps to spectacular success using goals, values, vision, and rewards - Kleinman, Dan (Career Press, 2008)
All Star Sales Teams focuses on molding the sales team into an organization's most productive nucleus. This book uniquely integrates critical development, organizational, and compensation concepts into practical, day-to-day processes. It also answers eight key questions that define successful sales and reward structures: -What methods most clearly communicate sales objectives? -How do you make sure that new products or services reinforce the organization's vision, strategy, and operating style? -What critical information does management need about how the marketplace rewards comparable delivery teams? -What tactics boost the effectiveness of sales rewards? -How can leaders maximize sales management strengths and neutralize weaknesses? -How does a company fully engage its sales representatives? -What functional areas ought to participate in designing sales rewards? -How can an organization minimize design complexity? This comprehensive book benefits anyone who manages a sales force, influences their company's strategy and staff productivity, or is critical in sustaining the culture of selling throughout an organization. It also provides a needed blueprint for achieving a dynamic sales environment and a satisfied and productive team of selling all-stars. Since 1990, Dan Kleinman has been an independent consultant for a broad spectrum of regional, national and international companies, providing an integrated package of performance, organizational planning and reward-system design services. While his client list includes Fortune 500 companies, Kleinman focuses most of his attention on offering support to small and mid-sized organizations that form the bulk of the business community. Prior to consulting, he spent 20 years managing a variety of human resource functions for Wells Fargo, AT & T and Charles Schwab. He has taught compensation principles for the American Compensation Association (now World at Work) and the American Banking Association's graduate school, written for and interviewed by trade journals and INC. magazine, and remains a sought-after presenter at various regional and national industry associations.